1996
DOI: 10.1074/jbc.271.10.5301
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of ob mRNA and Protein by Glucocorticoids and cAMP

Abstract: Regulation of obese gene (ob) expression in ob/ob and db/db mice and in cultured rat adipocytes was examined. It has been demonstrated that exogenous human OB protein (leptin) treatment reduces food intake and weight gain, as well as insulin, glucose, and corticosterone levels in ob/ob mice. In the present report we show that leptin treatment down-regulates endogenous adipose ob mRNA. However, treatment of isolated rat adipocytes with 100 ng/ml human or murine leptin had no direct effect on expression of endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
278
4
16

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(332 citation statements)
references
References 28 publications
30
278
4
16
Order By: Relevance
“…Interestingly in the present study, reduction of leptin was observed only in the third week of sleep reduction and coincided with an increase in bodyweight, which initially appears counterintuitive but corresponds well to what is found in cohort studies (reviewed by [40]). Leptin expression may be inhibited directly by catecholamines [41] . The effects of lowered levels 10 of leptin on hypothalamic centres regulating appetite, would potentially lead to increased food intake and weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly in the present study, reduction of leptin was observed only in the third week of sleep reduction and coincided with an increase in bodyweight, which initially appears counterintuitive but corresponds well to what is found in cohort studies (reviewed by [40]). Leptin expression may be inhibited directly by catecholamines [41] . The effects of lowered levels 10 of leptin on hypothalamic centres regulating appetite, would potentially lead to increased food intake and weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…TZDs consistently suppress leptin expression in rodent fat in vivo and in vitro (Table 1) [113,114,115,116]. Furthermore, β-adrenergic activation rapidly decreases leptin expression and secretion in primary adipocytes in vitro and mice in vivo (Table 1) [117,118]. Insulin is a potent activator of leptin mRNA expression and protein secretion [49] and it is plausible that insulin is the major mediator of increased post-prandial leptin concentrations (Table 1) [119,120,121].…”
Section: Leptinmentioning
confidence: 99%
“…Insulin is a potent activator of leptin mRNA expression and protein secretion [49] and it is plausible that insulin is the major mediator of increased post-prandial leptin concentrations (Table 1) [119,120,121]. Furthermore, glucocorticoids stimulate leptin expression and secretion in vivo and in vitro (Table 1) [49,118,122]. Of interest, this increase in leptin synthesis can be reversed by TZD treatment in humans [123].…”
Section: Leptinmentioning
confidence: 99%
“…In rodents, it has been reported that sympathetic activation, cAMP and b-receptor agonist down-regulate leptin gene expression and lower the plasma leptin level accompanied by an increase in lipolysis (Auwerx & Staels, 1998;Slieker et al, 1996;Mantzoros et al, 1996). In vitro studies demonstrated that NEFA inhibits leptin gene transcription in 3T3-L1 adipocytes (Rentsch & Chiesi, 1996), and that elevated intracellular NEFA induced by acyl-CoA synthase inhibitor down-regulates leptin synthesis and secretion in primary cultured rat adipocytes (Shintani et al, 2000).…”
Section: Clinical Implications Of Leptinmentioning
confidence: 99%
“…These observations strongly indicate the presence of leptin resistance in human obesity Heek et al, 1997;Arch et al, 1998;Beaufrere & Morio, 2000). In addition to the regulation associated with adipose tissue mass, leptin production is known to be regulated by such factors as peripheral nutritional status (Kolaczynski et al, 1996a,b;Boden et al, 1996;Reseland et al, 2001), sympathetic nerve activity (Auwerx & Staels, 1998;Slieker et al, 1996;Mantzoros et al, 1996), and a series of humoral factors (Auwerx & Staels, 1998).…”
Section: Introductionmentioning
confidence: 98%